2011
DOI: 10.3109/01443615.2011.598971
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of eNOS and ACE gene polymorphisms and risk of pre-eclampsia in women

Abstract: A meta-analyses of endothelial nitric oxide synthase (eNOS) and angiotensin-converting enzyme (ACE) gene polymorphisms in pre-eclampsia was performed. We shortlisted 33 studies (17 for ACE; 16 for eNOS gene polymorphisms), of which 29 articles (16 for ACE and 15 for eNOS) were analysed. Overall, 1,620 cases with pre-eclampsia and 2,158 controls were analysed for intron 16 insertion-deletion polymorphism in ACE gene. A total of 1,610 subjects with pre-eclampsia and 2,875 controls were analysed for the Glu298Asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
0
23
0
2
Order By: Relevance
“…6,7 There are controversial reports from different populations related to the role of ACE I/D polymorphism in the pathogenesis of preeclampsia. 1,3,[8][9][10][11][12][13][14][15][16][17] Also, in a few studies the association of AT1R A1166C polymorphism with preeclampsia has been examined. [8][9][10]17 A positive relationship between the degree of oxidative stress and the clinical severity of preeclampsia has been reported, suggesting that the toxic effects of lipoperoxide lead to hypertension, endothelial damage and leukocyte activation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 There are controversial reports from different populations related to the role of ACE I/D polymorphism in the pathogenesis of preeclampsia. 1,3,[8][9][10][11][12][13][14][15][16][17] Also, in a few studies the association of AT1R A1166C polymorphism with preeclampsia has been examined. [8][9][10]17 A positive relationship between the degree of oxidative stress and the clinical severity of preeclampsia has been reported, suggesting that the toxic effects of lipoperoxide lead to hypertension, endothelial damage and leukocyte activation.…”
Section: Introductionmentioning
confidence: 99%
“…[12,14] Besides, the studies conducted in the populations of India, China, and Colombia, revealed no significant effect of I/D ACE on the development of preeclampsia. [11,16,19] The observed inconsistency in the above results can be explained by interpopulation and interethnic differences in the distribution of the I/D polymorphism: allele D is predominant in Caucasians from Europe, Australia, and the USA, whereas allele I is more prevalent among Chinese and Indians. [24][25][26][27] …”
Section: Discussionmentioning
confidence: 82%
“…[8][9][10] The available data on the relationship between the polymorphism of ACE gene and the risk of preeclampsia development are contradictory. [11][12][13][14][15][16][17][18][19][20] In this regard, further research is needed to study the role of I/D ACE locus in the development of this complication of pregnancy.…”
Section: Original Articlementioning
confidence: 99%
“…Su et al 25 performed a metaanalysis to investigate the association of eNOS Glu298Asp gene polymorphism with recurrent pregnancy loss (RPL), and reported that eNOS Glu298Asp gene polymorphism was significantly associated with RPL. Shaik et al 26 reported that eNOS Glu298Asp gene polymorphism was not associated with the risk of pre-eclampsia in women by meta-analysis method. In our meta-analysis, we explore the relationship between eNOS Glu298Asp gene polymorphism and ESRD risk.…”
Section: Discussionmentioning
confidence: 99%